(untitled) (Revista BOEM, 2024)
This article aims to investigate the teachers’ perception regarding the production and use of digital cartoons in the teaching and learning process. To do so, we invited teachers of Science and Mathematics from the public school of the municipality of Tangará da Serra for a cartoon production training. From the pedagogical point of view, the intention is to discuss possibilities of use of Digital Technologies (TD) in pedagogical practices. Theoretically, we support authors who discuss digital technologies, teacher training and the use of cartoons in the teaching and learning process. Regarding the adopted methodology, we opted for the qualitative approach research, and for data analysis were performed through open questionnaires, interviews and observation during training. The results gave indications that the cartoons can contribute in the process of teaching and learning, presenting itself as a potentiator of the dialogue between teacher and student, in the production of knowledge in a playful, motivating and instigating way.